PEMBENTUKAN GENERASI PETANI ENTREPRENEUR Sketsa Etnografi Praktik Governmentality di SMK Pertanian - Purnomo, Taufik Agus (Sunari Penjor : Journal of Anthropology; Vol 8 No 2 (2024): Volume 8. No. 2. September 2024, 2024)
This thesis describes the practice of Agriculture Vocational Highschool in relation on the establishment generation of entrepreneurs in the school. By borrowing the concept of homo economicus was initiated and governmentality by Foucault, I examine how children are disciplined through a variety of techniques. Internalization ideology of entrepreneurship in the school of agriculture in my findings has been to deny the concept of vocational agriculture itself as hope for the next generation of farmers through education or minimal increase in interest in the younger generation to farm does not occur. Concept of entrepreneur and governmentality used to investigate and dismantle the process of the formation of character that took place in this vocational school. By using these two concepts can be seen that the activities in the school would produce a generation of business-oriented. Internalization of subject characters goes through the learning in the classroom, field work in the garden, to the extracurricular activities have formed the subjects mannered, obedient, disciplined, competitive spirit, religious, as well as individualistic.